16. EVALUATION OF THE EFFICACY OF CAO BAN LONG CAPSULES IN TREATING ERECTILE DYSFUNCTION (ED) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the efficacy of Cao Ban Long capsules in treating erectile dysfunction (ED) through a non-controlled before-after study. Methods: 30 men with ED (aged 28-65) were enrolled. In addition to being divided into groups according to the study objectives, these patients were also divided into groups according to traditional Chinese medicine patterns based on clinical examination. All patients were administered Cao Ban Long capsules 2 capsules/day for 8 weeks. ED symptoms were assessed using the IIEF-5 score before, after 4 weeks, and after 8 weeks of capsule use. All patients were monitored for adverse events and quality of life. Results: The mean IIEF-5 score increased significantly from 11.8 points before treatment to 16.8 points after 4 weeks (p < 0.05) and 18.3 points after 8 weeks (p < 0.05). The best results were seen in patients in the Qi and Blood Deficiency group with an IIEF-5 score of 18.4 after 8 weeks of treatment (p
Keywords: Erectile dysfunction, Cao Ban Long.